Low-porosity high-compaction sodium iron phosphate-diphosphate positive electrode material and preparation method thereof

CN123017960APending Publication Date: 2026-10-30NANJING LITHIUM SOURCE NANO TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611033218.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]因此,如何克服NFPP正极材料采用传统烧结工艺出现的大孔隙缺陷是本领域亟需解决的技术问题

Benefits of technology

[0020]本发明的有益效果是,本低孔隙高压实磷酸焦磷酸铁钠正极材料及其制备方法,通过制备Na4Fe3P4O15前驱体,在低温烧结过程中消耗大量产气基团,降低了成品二次球体的孔隙率,增强了颗粒间的致密性;此外,螯合剂的引入有效减少了砂磨时长,且在二次砂磨中混合非金属元素使二次烧结过程中不仅抑制了铁元素的氧化并促进纯相形成,同时非金属元素的引入进一步增加了内部局域电网数量,促进了离子和电子的传输。相较于传统体系,该体系所需碳含量较少,赋予材料更高的致密性增加其压实至2.21g/cm3,而且在0.1C电流密度下展现出最高充电比容量120.1 mAh g-1和最高放电比容量106.0 mAh g-1。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017960A_ABST
    Figure CN123017960A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of sodium-ion battery technology, specifically relating to a low-porosity, high-pressure sodium iron pyrophosphate cathode material and its preparation method. The molecular formula of the sodium iron pyrophosphate cathode material is Na4Fe3P. 4‑a X a O 15 / C; where X is a nonmetallic element, and the value of a ranges from 0.1 to 0.5. The preparation method includes the following steps: S1, Na4Fe3P4O 15 Preparation of the precursor: Iron source, sodium source, phosphorus source, and chelating agent are stoichiometrically mixed in water, ground, and then the mixture is sprayed in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to evaporate the water and obtain a spray material. This material is then sintered in a nitrogen atmosphere at 200-400℃ to obtain the desired product; S2, Na4Fe3P 4‑ a X a O 15 Preparation of / C: Add Na4Fe3P4O 15 After the precursor, carbon source and inorganic non-metallic powder are mixed evenly, they are ground and discharged. Then, the water is evaporated in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to obtain a spray material. Finally, it is sintered in a nitrogen atmosphere at 500-600℃ to obtain the final product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a low-porosity, high-pressure iron phosphate sodium pyrophosphate cathode material and its preparation method. Background Technology

[0002] With the large-scale development of clean energy, the development of low-cost, environmentally friendly, and wide-temperature-range adaptable electrochemical energy storage systems has become a common focus of industry and scientific research. Although lithium-ion batteries have been widely used due to their high energy density and long cycle life, their limited resources restrict the long-term development of large-scale energy storage. Sodium-ion batteries are considered one of the ideal alternatives due to the abundance of sodium resources (approximately 420 times that of lithium in the Earth's crust), low cost, and wide operating temperature range.

[0003] Among numerous cathode materials, the polyanionic compound Na4Fe3(PO4)2P2O7 (NFPP) stands out due to its stable three-dimensional framework, moderate operating voltage (approximately 3.1 V), and high theoretical capacity (129 mAh·g). -1 With advantages such as low volumetric strain, it is recognized as the technology route with the greatest potential for industrialization.

[0004] However, the intrinsic electron / ionic conductivity and low compaction density of NFPP currently hinder its further commercial application. At present, cathode materials produced by traditional sintering processes have large pores, and the use of high carbon sources not only reduces the overall active material content but also increases the porosity, thereby reducing the material's electrochemical performance and compaction density.

[0005] Therefore, how to overcome the large porosity defects that occur when using traditional sintering processes for NFPP cathode materials is a technical problem that urgently needs to be solved in this field.

[0006] It should be noted that the information disclosed in this background section is only for understanding the background technology of the present application concept, and therefore, the above description is not considered to constitute prior art information. Summary of the Invention

[0007] This disclosure provides at least one low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material and its preparation method.

[0008] In a first aspect, embodiments of this disclosure provide a sodium iron pyrophosphate cathode material, wherein the molecular formula of the sodium iron pyrophosphate cathode material is Na4Fe3P. 4-a X a O 15 / C; where X is a nonmetallic element and the value of a ranges from 0.1 to 0.5.

[0009] In one alternative implementation, X is S or Se.

[0010] Secondly, this disclosure also provides a method for preparing a sodium iron pyrophosphate cathode material, comprising the following steps: S1, Na4Fe3P4O 15 Preparation of the precursor: Iron source, sodium source, phosphorus source, and chelating agent are mixed in water according to stoichiometry, ground, and then the water is evaporated in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to obtain a spray material. This material is then sintered in a nitrogen atmosphere at 200-400℃ to obtain the desired product; S2, Na4Fe3P 4-a X a O 15 Preparation of / C: Add Na4Fe3P4O 15 After the precursor, carbon source and inorganic non-metallic powder are mixed evenly, they are ground and discharged. Then, the water is evaporated in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to obtain a spray material. Finally, it is sintered in a nitrogen atmosphere at 500-600℃ to obtain the final product.

[0011] In one alternative embodiment, the iron source includes one or more of iron oxide, ferric phosphate, ferrous sulfate, ferric sulfate, ferric oxalate, and metallic iron powder.

[0012] In one optional embodiment, the sodium source includes one or more of sodium carbonate, sodium hydroxide, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium bicarbonate, sodium sulfate, sodium fluoride, sodium citrate, sodium nitrate, and sodium oxalate.

[0013] In one optional embodiment, the phosphorus source includes one or more of phosphoric acid, iron phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0014] In one alternative embodiment, the chelating agent includes one or more of oxalic acid, tartaric acid, malic acid, salicylic acid, and ethylenediaminetetraacetic acid.

[0015] In one optional embodiment, the inorganic non-metallic powder includes one or more of selenium powder, selenium dioxide, sodium fluoride, sodium selenate, and sulfur powder.

[0016] In one optional embodiment, the amount of carbon source added accounts for 5% to 10% of the total mass of the iron source, sodium source, phosphorus source, and carbon source; the carbon source includes one or more of glucose, sucrose, citric acid, starch, ascorbic acid, cyclodextrin, and polyethylene glycol.

[0017] In one optional embodiment, the particle size range of the grinding output in S1 is 0.3 to 0.5 μm; and the particle size range of the grinding output in S2 is 0.2 to 0.3 μm.

[0018] In one optional embodiment, the heating rate during sintering in S1 is no higher than 5°C·min. -1 The sintering time is 8–12 hours; the heating rate in S2 is no higher than 2 °C·min. -1 The sintering time is 8 to 12 hours.

[0019] Thirdly, embodiments of this disclosure also provide a sodium battery, including the sodium iron pyrophosphate cathode material as described above.

[0020] The beneficial effects of this invention are that the low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material and its preparation method, through the preparation of Na4Fe3P4O 15 The precursor consumes a large number of gas-generating groups during low-temperature sintering, reducing the porosity of the finished secondary spheres and enhancing the compactness between particles. Furthermore, the introduction of the chelating agent effectively reduces the milling time, and the mixing of non-metallic elements during secondary milling not only inhibits iron oxidation and promotes pure phase formation during secondary sintering, but also further increases the number of internal localized electrical networks, promoting ion and electron transport. Compared to traditional systems, this system requires less carbon, imparting higher compactness to the material and increasing its compaction to 2.21 g / cm³. 3 Moreover, it exhibits the highest charging specific capacity of 120.1 mAh g at a current density of 0.1C. -1 With a maximum discharge specific capacity of 106.0 mAh g -1 .

[0021] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention are realized and obtained through the structures particularly pointed out in the description and the drawings.

[0022] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings. Attached Figure Description

[0023] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0024] Figure 1 Na4Fe3P provided in the embodiments of this disclosure 3.8 Se 0.2 O 15SEM image of / C spray material; Figure 2 Na4Fe3P provided in the embodiments of this disclosure 3.8 Se 0.2 O 15 / C sintered sample CP diagram; Figure 3 Na4Fe3P provided in the embodiments of this disclosure 3.8 Se 0.2 O 15 XRD pattern of / C sintered sample; Figure 4 Na4Fe3P provided in the embodiments of this disclosure 3.8 Se 0.2 O 15 The first charge-discharge curve of the / C sintered sample. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] As used herein, the phrases “in one embodiment,” “according to one embodiment,” “in some embodiments,” etc., generally refer to the fact that a particular feature, structure, or characteristic following the phrase can be included in at least one embodiment of this disclosure. Therefore, a particular feature, structure, or characteristic can be included in more than one embodiment of this disclosure, such that these phrases do not necessarily refer to the same embodiment. As used herein, the terms “example,” “exemplary,” etc., are used to “serve as an example, instance, or illustration.” Any implementation, aspect, or design described herein as “example” or “exemplary” is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. Rather, the use of the terms “example,” “exemplary,” etc., is intended to present concepts in a specific manner.

[0027] In this document, exemplary embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as “at least one of…” modify the entire list of elements when following a list of elements, rather than individual elements in the list. For example, the expression “at least one of a, b, and c” should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0028] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0029] This disclosure provides a sodium iron pyrophosphate cathode material, wherein the molecular formula of the sodium iron pyrophosphate cathode material is Na4Fe3P. 4-a X a O 15 / C; where X is a nonmetallic element and the value of a ranges from 0.1 to 0.5.

[0030] In some embodiments, specifically, X is S or Se.

[0031] This disclosure also provides a method for preparing sodium iron pyrophosphate cathode material, including the following steps: S1, Na4Fe3P4O 15 Preparation of the precursor: Iron source, sodium source, phosphorus source, and chelating agent were stoichiometrically mixed in water, ground in a sand mill, and then the mixture was sprayed to obtain a spray material by evaporating the water in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃. The material was then sintered in a nitrogen atmosphere at 200-400℃ to obtain the precursor; S2, Na4Fe3P 4-a X a O 15 Preparation of / C: Add appropriate amount of Na4Fe3P4O 15 After the precursor, carbon source and inorganic non-metallic powder are mixed evenly, they are ground in a sand mill and discharged. Then, the water is evaporated in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to obtain a spray material. Finally, it is sintered in a nitrogen atmosphere at 500-600℃ to obtain the final product.

[0032] In some embodiments, specifically, the iron source includes one or more of iron oxide, ferric phosphate, ferrous sulfate, ferric sulfate, ferric oxalate, and metallic iron powder.

[0033] In some embodiments, the sodium source specifically includes one or more of sodium carbonate, sodium hydroxide, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium bicarbonate, sodium sulfate, sodium fluoride, sodium citrate, sodium nitrate, and sodium oxalate.

[0034] In some embodiments, specifically, the phosphorus source includes one or more of phosphoric acid, iron phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0035] In some embodiments, the chelating agent specifically includes one or more of oxalic acid, tartaric acid, malic acid, salicylic acid, and ethylenediaminetetraacetic acid.

[0036] In some embodiments, specifically, the non-metallic compound includes one or more of selenium powder, selenium dioxide, sodium selenate, and sulfur powder.

[0037] In some embodiments, specifically, the amount of carbon source added accounts for 5% to 10% of the total mass of the iron source, sodium source, phosphorus source, and carbon source; the carbon source includes one or more of glucose, sucrose, citric acid, starch, ascorbic acid, cyclodextrin, and polyethylene glycol.

[0038] In some embodiments, specifically, the particle size range of the grinding output in S1 is 0.3 to 0.5 μm; and the particle size range of the grinding output in S2 is 0.2 to 0.3 μm.

[0039] In some embodiments, specifically, the heating rate of sintering in S1 is no higher than 5°C·min. -1 The sintering time is 8–12 hours; the heating rate in S2 is no higher than 2 °C·min. -1 The sintering time is 8 to 12 hours.

[0040] This disclosure also provides a sodium battery, including the sodium iron pyrophosphate cathode material as described above.

[0041] Example 1: The low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material described in this example has the chemical formula Na4Fe3P. 3.8 Se 0.2 O 15 / C, the preparation method includes the following steps: Na4Fe3P4O 15 Precursor preparation: Ferric phosphate, sodium carbonate, ammonium dihydrogen phosphate, and oxalic acid were weighed according to stoichiometry and mixed in water. After stirring evenly, the mixture was ground in a sand mill to a particle size of 0.4 μm. The resulting product was then evaporated in a spray tower with an inlet air temperature of 220°C and an outlet air temperature of 100°C to obtain a spray powder. Finally, the powder was placed in a nitrogen atmosphere with a heating rate set to 5°C / min. -1 The mixture is then heated to 300℃ and sintered for 4 hours to obtain the final product.

[0042] Na4Fe3P 3.8 Se 0.2 O 15 / C Preparation: Add 1 mol Na₄Fe₃P₄O 15 The precursor, 8% glucose (by total mass of ferric phosphate, sodium carbonate, ammonium dihydrogen phosphate, and glucose), and 0.2 mol selenium powder were mixed in water and stirred evenly. The mixture was then ground in a sand mill to a particle size of 0.25 μm. The resulting product was then evaporated in a spray tower with an inlet air temperature of 220°C and an outlet air temperature of 100°C to obtain a spray powder. Finally, the powder was placed in a nitrogen atmosphere with a heating rate set at 2°C / min. -1 The product is obtained by sintering at 500℃ for 8 hours.

[0043] Example 2: The low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material described in this example has its selenium powder doping amount reduced to 0.1 mol, and is named Na4Fe3P. 3.9 Se 0.1 O 15 / C.

[0044] The preparation method is the same as in Example 1.

[0045] Example 3: The low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material described in this example has its selenium powder doping amount increased to 0.3 mol, and is named Na4Fe3P. 3.7 Se 0.3 O 15 / C The preparation method is the same as in Example 1.

[0046] Example 4: The low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material described in this example has its selenium doping replaced with sulfur doping (0.2 mol doping amount), and is named Na4Fe3P. 3.8 S 0.2 O 15 / C.

[0047] Example 5: The low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material described in this example has its sulfur powder doping reduced to 0.1 mol, and is named Na4Fe3P. 3.9 S 0.1 O 15 / C.

[0048] Example 6: The low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material described in this example has its sulfur powder doping increased to 0.3 mol, and is named Na4Fe3P. 3.7 S 0.3 O 15 / C.

[0049] The preparation method is the same as in Example 1.

[0050] Comparative Example 1: The difference from Example 1 is that oxalic acid was replaced with citric acid.

[0051] Comparative Example 2: The difference from Example 1 is that ferric phosphate was replaced with a mixed iron source of ferric phosphate and ferrous oxalate in a mass ratio of 1:1.

[0052] Comparative Example 3: The difference from Example 1 is that ferric phosphate was replaced with a mixed iron source of ferric phosphate and ferric nitrate in a mass ratio of 1:1.

[0053] Comparative Example 4: Preparation of sodium iron pyrophosphate cathode material by one-time sintering. The specific preparation method is as follows: A certain amount of iron phosphate, sodium carbonate, ammonium dihydrogen phosphate, oxalic acid, and glucose were weighed and mixed in water. After stirring evenly, the mixture was ground in a sand mill until the particle size was 0.25 μm. The material was then discharged and the water was evaporated in a spray tower with an inlet air temperature of 220°C and an outlet air temperature of 100°C to obtain the spray material. Subsequently, the spray material was placed in a nitrogen atmosphere and the heating rate of the low-temperature section was set to 5°C / min. -1 After sintering at 300℃ for 4 hours, the heating rate of the high-temperature section was set to 5℃ / min. -1 Then, heat the temperature to 500℃ and sinter for 8 hours.

[0054] As can be seen from the attached figures and tables: The morphology and structure of the cathode material were characterized using scanning electron microscopy (SEM) and wafer probe microanalysis (CP), such as... Figure 1 and Figure 2 As shown. The sample spray exhibits a spherical morphology and low internal porosity, thus demonstrating high compaction. X-ray diffraction (XRD) tests were performed, as shown... Figure 3 As shown, the diffraction peaks of NFPP are consistent with those of NFPP, and the absence of an inert sodium iron phosphate phase reveals the synthesis of its pure phase. This can be attributed to the effective promotion of pure phase formation by non-metallic elements during the secondary sintering process. Furthermore, all diffraction peaks of NFPP exhibit high intensity and sharpness, revealing a higher degree of crystallinity and a more ordered crystal arrangement. This significantly improves the electronic conductivity and structural stability of the material, which can be attributed to the doping of non-metallic elements, thereby enhancing the electrochemical performance of the material.

[0055] Electrical performance testing: A coin cell was assembled using a glass fiber separator and sodium perchlorate as the electrolyte, with the cathode material, Super-P, and PVDF coated on aluminum foil in a 9:1:1 ratio. Testing was conducted on a Blue Electric testing system with a voltage window of 2.0-4.0V and 1C = 120mAh / g. The results are as follows: Figure 4 As shown, the charge-discharge curves of this cathode material at a current density of 0.1C show a maximum charge specific capacity of 120.1 mAh g⁻¹. -1 The highest discharge specific capacity can reach 106.0 mAh g. -1 .

[0056] Table 1 Performance test data of Comparative Examples 1-4 and Examples 1-6

[0057] Table 1 shows that, compared to the low compaction and poor performance of single-sintering, NFPP prepared via precursor exhibits superior electrochemical performance and high compaction, which can be attributed to the low-temperature preparation of Na4Fe3P4O. 15The precursor consumes gas-producing groups (such as CO3) in the raw materials. 2- C2O4 2- C6H5O7 3- This process improves the particle density and low porosity of subsequent sintering. Subsequent secondary milling introduces non-metallic elements, inhibiting iron oxidation and promoting pure phase formation, while also improving the intrinsic electronic / ionic conductivity of the material. Furthermore, reducing the carbon content lowers the proportion of inert carbon in the composite material, further enhancing particle density and improving the material's charge / discharge capability. Therefore, Na4Fe3P... 3.8 Se 0.2 O 15 / C exhibits excellent charge specific capacity of 120.1 mAh g at a current density of 0.1C. -1 Discharge specific capacity 106.0 mAh g -1 And a high compaction density of 2.21 g / cm³ was obtained. 3 Other embodiments demonstrate optimal doping elements and ratios, with elemental selenium doping yielding the best electrochemical performance, resulting from the highest electronic / ionic conductivity.

[0058] Specifically, in Comparative Example 1, oxalic acid was replaced with citric acid. Oxalate decomposes at low temperatures, releasing only CO and CO2. The decomposition temperature range is narrow, and gas production is concentrated in the low-temperature sintering stage of the precursor, allowing for early gas release. No additional gas is generated during the secondary high-temperature sintering, resulting in particles with fewer internal pores and higher density. In contrast, citric acid decomposes at a higher temperature and is incompletely decomposed at low temperatures, forming numerous micropores between particles. This ultimately reduces the compacted density of the particles from 2.21 g / cm³. 3 Reduced to 2.05 g / cm³ 3 Furthermore, due to the incomplete decomposition of citrate at low temperatures, some residual carbon can cause poor uniformity of subsequent carbon coating, resulting in slightly lower electrochemical performance.

[0059] Specifically, in Comparative Example 2, ferric phosphate was replaced with a mixed iron source of ferric phosphate and ferrous oxalate. Ferrous oxalate decomposes incompletely at low temperatures, and the oxalate ions are difficult to completely decompose. Therefore, during the subsequent secondary sintering process, some gas is released, resulting in weaker compaction and reduced density. Furthermore, at high temperatures, ferrous oxalate easily forms elemental Fe and FeO. During the secondary sintering process, the doping of non-metallic elements such as Se cannot completely suppress the oxidation of low-valence iron, forming an inert sodium ferric phosphate impurity phase. This reduces the proportion of the active NFPP main phase, decreasing the effective active material and thus lowering performance.

[0060] Specifically, in Comparative Example 3, ferric phosphate was replaced with a mixed iron source of ferric phosphate and ferric nitrate. Ferric nitrate is difficult to completely decompose at low temperatures, which leads to the release of some gas during the secondary sintering process, thereby weakening the compactness of the particles and affecting the phase crystallization process of the material, ultimately affecting the compaction and performance of the material.

[0061] Specifically, Comparative Example 4 underwent only one sintering step. Due to the large amount of gas emitted during the sintering process, significant porosity existed between the particles. This porosity could not be eliminated by secondary milling, resulting in the lowest compaction density among all groups. Furthermore, the large amount of gas emitted caused the internal pressure of the material to continue to rise, disrupting the sintering atmosphere and affecting the phase crystallization process of the material, ultimately leading to poor electrochemical performance.

[0062] In summary, this low-porosity, high-pressure solid iron phosphate sodium pyrophosphate cathode material and its preparation method utilize Na4Fe3P4O 15 During low-temperature sintering, the precursor consumes a large number of gas-generating groups, reducing the porosity of the finished secondary spheres and enhancing the compactness between particles. Furthermore, the introduction of the chelating agent effectively reduces the milling time, and the mixing of non-metallic elements during secondary milling not only inhibits iron oxidation and promotes pure phase formation during secondary sintering, but also further increases the number of internal localized electrical networks, promoting ion and electron transport. Compared to traditional systems, this system requires less carbon, imparting higher compactness to the material and increasing its compaction to 2.21 g / cm³. 3 Moreover, it exhibits the highest charging specific capacity of 120.1 mAh g at a current density of 0.1C. -1 With a maximum discharge specific capacity of 106.0 mAh g -1 .

[0063] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A sodium iron pyrophosphate cathode material, characterized in that, The molecular formula of the sodium iron pyrophosphate cathode material is Na₄Fe₃P. 4-a X a O 15 / C; Where X is a nonmetallic element, and the value of a ranges from 0.1 to 0.

5.

2. The sodium iron pyrophosphate cathode material as described in claim 1, characterized in that, X is S or Se.

3. A method for preparing a sodium iron pyrophosphate cathode material, characterized in that, Includes the following steps: S1, Na4Fe3P4O 15 Preparation of precursor: Iron source, sodium source, phosphorus source and chelating agent are mixed in water according to stoichiometry, ground and discharged, and then the water is evaporated in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to obtain spray material, which is then sintered in a nitrogen atmosphere at 200-400℃. S2, Na4Fe3P 4-a X a O 15 Preparation of / C: Add Na4Fe3P4O 15 After the precursor, carbon source and inorganic non-metallic powder are mixed evenly, they are ground and discharged. Then, the water is evaporated in a spray tower with an inlet air temperature of 180-250℃ and an outlet air temperature of 80-110℃ to obtain a spray material. Finally, it is sintered in a nitrogen atmosphere at 500-600℃ to obtain the final product.

4. The method for preparing the sodium iron pyrophosphate cathode material as described in claim 3, characterized in that, The iron source includes one or more of the following: iron oxide, ferric phosphate, ferrous sulfate, ferric sulfate, ferric oxalate, and metallic iron powder. The sodium source includes one or more of sodium carbonate, sodium hydroxide, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium bicarbonate, sodium sulfate, sodium fluoride, sodium citrate, sodium nitrate, and sodium oxalate. The phosphorus source includes one or more of phosphoric acid, iron phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

5. The method for preparing the sodium iron pyrophosphate cathode material as described in claim 3, characterized in that, The chelating agent includes one or more of oxalic acid, tartaric acid, malic acid, salicylic acid, and ethylenediaminetetraacetic acid.

6. The method for preparing the sodium iron pyrophosphate cathode material as described in claim 3, characterized in that, The inorganic non-metallic powder includes one or more of selenium powder, selenium dioxide, sodium selenate, and sulfur powder.

7. The method for preparing the sodium iron pyrophosphate cathode material as described in claim 3, characterized in that, The amount of carbon source added accounts for 5% to 10% of the total mass of the iron source, sodium source, phosphorus source, and carbon source; The carbon source includes one or more of glucose, sucrose, citric acid, starch, ascorbic acid, cyclodextrin, and polyethylene glycol.

8. The method for preparing the sodium iron pyrophosphate cathode material as described in claim 3, characterized in that, The particle size range of the grinding output in S1 is 0.3 to 0.5 μm; The particle size range of the grinding output in S2 is 0.2 to 0.3 μm.

9. The method for preparing the sodium iron pyrophosphate cathode material as described in claim 3, characterized in that, The sintering heating rate in S1 is no higher than 5°C·min. -1 The sintering time is 8–12 hours; The sintering heating rate in S2 is no higher than 2℃·min. -1 The sintering time is 8 to 12 hours.

10. A sodium battery, characterized in that, Including the sodium iron pyrophosphate cathode material as described in claim 1 or 2.